A review on occurrences, challenges and detection methods of pesticides: recent treatment technologies - Lopez-Maldonado, E. A.; Mahmoud, A. E. D.; Alfarra, F.; Can-Gueven, E.; Ciner, M. N.; Guvenc, S. Y.; Mansour, M.; Varank, G.; Ozcan, H. K.; Ghanbari, F.; Yusan, S.; Khan, N. A. (SPRINGER, 2025)
Pesticides, while vital for modern agriculture, pose significant risks due to residue accumulation in food and water. This review focuses on the critical aspects of pesticide detection and treatment, highlighting the latest techniques and their comparative advantages and disadvantages. We move beyond detailed insecticide formation to address the pressing need for effective monitoring and remediation. Current detection methods, such as gas and liquid chromatography/mass spectrometry, offer high accuracy but are often complex and expensive, limiting their suitability for rapid, large-scale industrial applications. To address this, we explore innovative approaches like surface-enhanced Raman spectroscopy swabs, including those utilizing nanoparticles for on-site pesticide detection in fruits and vegetables. These methods offer the potential for faster, more cost-effective screening. Regarding treatment, traditional physical, chemical, and biological methods, while useful, can be costly and generate secondary pollutants. We emphasize the challenge of removing persistent pesticides, such as atrazine, from water systems and advocate for the development of efficient, cost-effective on-site screening and treatment technologies. This review provides a comparative analysis of these detection and treatment methods, emphasizing the need for advancements that balance accuracy, cost-effectiveness, and environmental sustainability.
Keywords: Detection methods; Pesticide degradation; Nanotechnology; Advanced treatment technologies; ORGANOCHLORINE PESTICIDES; WASTE-WATER; NANO-COMPOSITE; ORGANIC CONTAMINANTS; REMOVAL; DISSIPATION; RESIDUES; SOIL; AIR; PHYTOREMEDIATION; Environmental Sciences & Ecology